Foreign Language Information Literacy Model in The Covid-19 Pandemic Era as an Effort to Prevent Hoaxes in Kediri City - Ayu Madona; Nurul Hanani (Didaktika Religia, 2020)
DuringÂ the Covid-19 pandemic,Â one of the abilities thatÂ every individualÂ must haveÂ is to be able toÂ understand well the information that is widespread onÂ digital platforms.Â The amount of information thatÂ uses English terms often creates pros and cons in society because of the inability toÂ understand the meaning contained in the text.Â Even though English is the language of connection that will bridge theÂ occurrence ofÂ interaction feedbackÂ globally. The focus of the author is to provide socialization and assistance to residentsÂ using anÂ ethnographicÂ approachÂ that combines historical methods, observation, and interviews.Â This aims toÂ explain the importance of understanding a foreign text from various disclosure of information with the assistance of literate culture as an actÂ preventive against hoaxes, especially for residents ofÂ the DistrictÂ Kaliombo,Â Kota Kediri. However, information can be a trigger for weak immunity andÂ affect people's thinking, language,Â and behavior.Â Linguistic PolitenessÂ will describe the characteristics of the community itselfÂ andÂ become aÂ major foothold in the act.Â Several pending findings resulted.